KONTRIBUSI TOKOH PEMIKIR EKONOMI ISLAM DI ERA KONTEMPORER - Nur Fadila; Moh Fitra; Nur Humairah Annisa; Wilda Ramadina; Jamaluddin Jamaluddin (El-Fata: Journal of Sharia Economics and Islamic Education, 2023)
This research aims to find out the figures of contemporary Islamic economic thought, among others; Baqr al Sadr, Abu Ya'la Al-Maududi, and Monzer Kahf. These Muslim thinkers are divided into three categories; first, experts in the field of fiqh so that the approach taken is legalistic and normative; second, modernist groups who are more courageous in providing interpretations of Islamic teachings in order to answer the problems faced by society today; third, practitioners or Muslim economists with Western educational backgrounds. They combine fiqh and economic approaches so that Islamic economics is conceptualized in an integrated manner. In fact, the construction of an Islamic economic system capable of delivering welfare and social justice must be built on the basis of aqidah and elaborated in great detail in the concepts of ownership, the role of the state, and distribution, including production and consumption. Even though the distribution of income in society is the most important thing in the construction of the Islamic economic system.